2023
DOI: 10.1097/cm9.0000000000002647
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin facilitates fear extinction in mice by promoting hippocampal neuroplasticity

Abstract: Background: Posttraumatic stress disorder (PTSD) and depression are highly comorbid. Psilocybin exerts substantial therapeutic effects on depression by promoting neuroplasticity. Fear extinction is a key process in the mechanism of first-line exposurebased therapies for PTSD. We hypothesized that psilocybin would facilitate fear extinction by promoting hippocampal neuroplasticity. Methods: First, we assessed the effects of psilocybin on percentage of freezing time in an auditory cued fear conditioning (FC) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Other study has shown that administration of a single dose of psilocybin (2.5 mg/kg, i.p. ), 30 min before extinction training, reduces the increase in the percentage of freezing rate induced by fear conditioning at 24 hr, 6 days, and 7 days after administration, probably by the promotion of hippocampal neuroplasticity (Du et al, 2023); and in line with this finding, we showed that all injections of Psilocybe cubensis (pretrain, posttrain, pretest) reduced freezing rate 24 hr after fear conditioning (and also 3 days except pretest injection, but not 21 days for all injections). Furthermore, psilocybin (2 mg/kg, 30 min before fear-conditioning test) significantly attenuate PTSD-like (freezing) behavior, 7 days after fear conditioning in rats (Hagsäter et al, 2021); although we showed that pretest (but not pretrain and posttrain) injection of Psilocybe cubensis extract did not reduce freezing.…”
Section: Discussionmentioning
confidence: 99%
“…Other study has shown that administration of a single dose of psilocybin (2.5 mg/kg, i.p. ), 30 min before extinction training, reduces the increase in the percentage of freezing rate induced by fear conditioning at 24 hr, 6 days, and 7 days after administration, probably by the promotion of hippocampal neuroplasticity (Du et al, 2023); and in line with this finding, we showed that all injections of Psilocybe cubensis (pretrain, posttrain, pretest) reduced freezing rate 24 hr after fear conditioning (and also 3 days except pretest injection, but not 21 days for all injections). Furthermore, psilocybin (2 mg/kg, 30 min before fear-conditioning test) significantly attenuate PTSD-like (freezing) behavior, 7 days after fear conditioning in rats (Hagsäter et al, 2021); although we showed that pretest (but not pretrain and posttrain) injection of Psilocybe cubensis extract did not reduce freezing.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, psilocybin promotes neurogenesis by rescuing the reduction in DCX and BrdU positive cells caused by fear conditioning-induced stress in the hippocampus ( Du et al, 2023 ; Zhao et al, 2024 ). Moreover, mice administered low doses of psilocybin have shown a swifter extinction of cued fear conditioning compared to those given higher doses.…”
Section: Potential Mechanisms Of Psilocybin Treatment For Admentioning
confidence: 99%
“…Studies on AD rats induced with streptozotocin have shown that the administration of 5-HT1A and 5-HT2A receptor agonists has significant neuroprotective effects on hippocampal neurons through anti-apoptotic and anti-inflammatory pathways ( Shahidi et al, 2019 ). Psilocybin, known for its mechanisms in promoting neuroplasticity, anti-inflammation, and improving functional connectivity of brain networks in the treatment of depression and other diseases, may hold potential benefits for patients with AD ( Nkadimeng et al, 2021 ; Daws et al, 2022 ; Du et al, 2023 ). Additionally, depression and anxiety are common mental symptoms of AD and can accelerate cognitive decline in AD patients ( Gallagher et al, 2018 ; Ma, 2020 ; Agüera-Ortiz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive inflexibility, or the inability to adapt thought or behavior to new environmental demands, is central to a wide range of neuropsychiatric disease 35,36 . Evidence from human, rodent, and molecular research converges on the hypothesis that psilocybin generates highly plastic brain states conducive to modifying circuits that underlie inflexible, maladaptive behaviors via 5HT2R and TrkB activation 2,17,[37][38][39][40][41][42][43][44] . Acute activation of cortical neurons by psychedelics induces synaptic AMPA receptor insertion, BDNF signaling, and consequent dendritic growth 40,43,45,46 .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from human, rodent, and molecular research converges on the hypothesis that psilocybin generates highly plastic brain states conducive to modifying circuits that underlie inflexible, maladaptive behaviors via 5HT2R and TrkB activation 2,17,[29][30][31][32][33][34][35][36] . Acute activation of cortical neurons by psychedelics induces synaptic AMPA receptor insertion, BDNF signaling, and consequent dendritic growth 32,35,37,38 . It is unknown how these molecular actions of psilocybin impact information processing in neural ensembles associated with aversive memories and maladaptive behavioral patterns.…”
Section: Introductionmentioning
confidence: 99%